2017
DOI: 10.1038/bjc.2017.111
|View full text |Cite
|
Sign up to set email alerts
|

Self-sampling to improve cervical cancer screening coverage in Switzerland: a randomised controlled trial

Abstract: Background:The aim of this study is to evaluate whether self-sampling can increase screening attendance of women who do not attend regular screening in Switzerland.Methods:Participants were proactively recruited in Geneva between September 2011 and November 2015. Women (25–69 years) who had not undergone CC screening in the last 3 years were considered eligible. Through a 1 : 1 ratio randomisation, enrolled participants were invited to either undergo liquid-based cytology, which was performed by a health-care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…While in a Norwegian trial, 94.1% of women tested positive attended follow up . In a Swiss study, there were 5.05% (95% CI: 3.1–8.1) women with a positive screen who did not attend triage and colposcopy . In an Australian study 75.7% of the hrHPV positive women had appropriate clinical follow‐up .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While in a Norwegian trial, 94.1% of women tested positive attended follow up . In a Swiss study, there were 5.05% (95% CI: 3.1–8.1) women with a positive screen who did not attend triage and colposcopy . In an Australian study 75.7% of the hrHPV positive women had appropriate clinical follow‐up .…”
Section: Discussionmentioning
confidence: 94%
“…19 In a Swiss study, there were 5.05% (95% CI: 3.1-8.1) women with a positive screen who did not attend triage and colposcopy. 20 In an Australian study 75.7% of the hrHPV positive women had appropriate clinical follow-up. 21 In a French study targeting a low-income population, only 41% of the women who tested positive for hrHPV had a follow up PAP smear taken.…”
Section: Discussionmentioning
confidence: 99%
“…After two independent reviewers screened in duplicate and gained consensus, 149 articles were pulled for full-text review. Of these, 33 studies (reported in 34 articles) were included in the review 21–54…”
Section: Resultsmentioning
confidence: 99%
“…Human papillomavirus (HPV) testing in self-collected cervicovaginal samples (HPV self-sampling for short) has been increasingly investigated as a potential screening alternative to standard physician-based sampling to complement primary cervical cancer screening programs by enhancing coverage among nonattendees. It has been implemented in the Netherlands (1) and Australia (2), and other countries, including the United States (3), United Kingdom (4), Norway (5), Denmark (6), and Switzerland (7), are evaluating its incorporation into national cervical screening programs (8). The utility of HPV self-sampling in cervical cancer screening is predicated on the availability of validated HPV assays (9).…”
Section: Introductionmentioning
confidence: 99%